REALIZATION OF STRATEGIC PLANNING IN IRAN’S HIGHER EDUCATION SYSTEM - Tafreshi, Seyed; Tavakoli, Hamdollah; Salajegheh, Sanjar (Revista Inclusiones, 2019)
This study investigated the status of strategic planning in Iran higher education system. It was an applied descriptive-survey study. The statistical population consisted of heads and deputies of the universities covered by the Ministry of Science, Research and Technology and the Ministry of Health, Medical Education and Islamic Azad University of Khorasan Razavi (N=320). 175 individuals were selected using cluster random sampling. For data collection, the standard questionnaire of Braison (2010) was used. The reliability coefficient was (0.910) using Cronbach’s alpha test. The face and content validity were evaluated using expert opinion and construct validity using confirmatory factor analysis. For statistical analysis of the data, one-variable t-test, skewness and kurtosis test, Friedman test and confirmatory factor analysis were used in Smart Pls, Spss software. The findings indicated that the status of implementation of strategic planning in the studied population was at an unfavorable level, and components of strategic planning are not ranked the same. The component of determining organizational duties had the highest rank among the components of implementation of the strategic planing and the components of initial agreement and strategic issues were ranked next (p-value <0.05). Given the unfavorable state of implementation of strategic plans, universities and higher education institutions are urged to correctly and timely implement the plans and eliminate existing obstaclesv.